2020
DOI: 10.33387/j.bilingual.v10i2.2530
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATING LEARNERS’ OBSTACLES IN SECOND LANGUAGE READING COMPREHENSION

Abstract: Skill in reading texts written in English as a foreign language constitutes a fundamental element of the establishment of English curriculum in Indonesia. The aim of this article is to investigate and explore the obstacles and difficulties faced by Indonesians in their learning activities which hampering the learners in gaining comprehension, and to view the pedagogy from the broader perspective on the theories of reading process. As the writer found, the learners are lack of language system understanding, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One of the skills that a learner must acquire in learning the English language is the ability to comprehend. Hence, the most significant reason affecting reading inefficiency among L2 learners is the lack of reading strategy (Sahmadan & Ajam, 2020). Given that the learners have prior knowledge of the target language, the effectivity will be shown based on the awareness set by the students (Yapp et al, 2021).…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…One of the skills that a learner must acquire in learning the English language is the ability to comprehend. Hence, the most significant reason affecting reading inefficiency among L2 learners is the lack of reading strategy (Sahmadan & Ajam, 2020). Given that the learners have prior knowledge of the target language, the effectivity will be shown based on the awareness set by the students (Yapp et al, 2021).…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…As Bulut (2017) pointed out that reading comprehension is a multi-step process that involves the reader's vocabulary knowledge, textual interaction, and application of comprehension strategies. The findings revealed that cultural background, English teaching and learning processes, and teaching and learning methodologies all influence the difficulties and problems that Indonesians encounter (Sahmadan, 2020).…”
Section: Introductionmentioning
confidence: 98%